Cardiovascular risk assessment: Missing albuminuria contributing to gender inequality - Patricia de Sequera; Javier Arias; Borja Quiroga; María Benavent; Fabio Procaccini; Iago Romero; Guillermo López; Javier Diez; Alberto Ortiz (Nefrología (English Edition))
Introduction: Chronic kidney disease (CKD) is associated with high cardiovascular disease (CVD) risk, and requires specific interventions to decreases CVD risk.The guidelines indicate that systematic global CVD risk assessment is recommended in individuals with any major vascular risk factor. The European Society Cardiology (ESC) guidelines, he European Renal Association (ERA) Council and the Spanish Society of Nephrology (S.E.N.) in collaboration with 15 Scientific Societies recommend assessing albuminuria in all these populations.We have evaluated current clinical practice regarding the assessment of CVD risk factors (blood pressure, albuminuria, serum cholesterol, glycemia and creatinine) in different adult health user populations, analyzing the results separately for men and women, given recent evidence on gender differences in the recognition, monitoring, and management of CKD. Methods: Observational, retrospective, non-interventional single center study performed in a hospital using Electronic Health Record (EHR) data. Results: Among 707,493 healthcare users, 612,619 were adults, and of these 332,943 (54.3%) females; 73,632 (12.0%) had DM and 121,445 (19.8%) hypertension. Mean (SD) age was 68.91 ± 21.4 years; 261,694 (36.9%) were older than 50 years.Only 8522 (1.39%) had undergone albuminuria testing as compared with 264,684 (43.21%) tested for serum creatinine, 140,492 (22.93%) for serum cholesterol, 263,381 (42.99%) for serum glucose, and 226,448 (36.96%) for blood pressure. Albuminuria was the only cardiovascular risk factor assessed more frequently in men than in women.Albuminuria, as other CVD risk factors, was more frequently assessed in patients with DM (6.71% of patients) or hypertension (4.81%), but albuminuria assessment remained suboptimal compared with 58–87% for other cardiovascular risk factors. For adults with diabetes or hypertension, albuminuria was assessed more frequently in men than in women.Albuminuria assessment in those older than 50 years was also suboptimal at 2.24%, as compared with 31–47% for other CVD risk factors.Albuminuria and EGFR are needed to screen for CKD, meaning that a urine test for albumin and creatinine and a serum test for creatinine are needed. To these, we may add assessment of blood pressure, serum cholesterol (for familial hypercholesterolemia) and serum glucose for Diabetes. Albuminuria was the only cardiovascular risk factor that was assessed more frequently in men (up to nearly 60% more frequently), indicating that screening for CKD and CVD risk in women is suboptimal. This result is surprisingly consistent across time and in all age groups. This is the first time that gender disparities in the assessment of albuminuria have been revealed. Conclusion: Albuminuria is assessed infrequently, even in patients with a high cardiovascular risk, especially in women. Resumen: Introducción: La enfermedad renal crónica (ERC) se asocia con un alto riesgo de enfermedad cardiovascular (ECV) y requiere intervenciones específicas para disminuir este riesgo.Las guías recomiendan una evaluación global sistemática del riesgo de ECV en personas con cualquier factor de riesgo vascular importante. Las guías de la Sociedad Europea de Cardiología (SEC), la Asociación Renal Europea (ERA) y la Sociedad Española de Nefrología (SEN), en colaboración con 15 sociedades científicas, recomiendan evaluar la albuminuria en todas estas poblaciones.Hemos evaluado la práctica clínica actual con respecto a la evaluación de los factores de riesgo de ECV (presión arterial, albuminuria, colesterol sérico, glucemia y creatinina) en diferentes poblaciones adultas de usuarios de salud, analizando los resultados por separado para los hombres y las mujeres, dada la evidencia reciente sobre las diferencias de género en el reconocimiento, el seguimiento y el tratamiento de la ERC. Métodos: Estudio observacional, retrospectivo, no intervencionista, unicéntrico, realizado en un hospital utilizando datos de la historia clínica electrónica. Resultados: De los 707.493 usuarios de atención sanitaria, 612.619 eran adultos. De ellos, 332.943 (54,3%) eran mujeres, 73.632 (12,0%) tenían DM y 121.445 (19,8%) tenían hipertensión. La edad media (DE) fue 68,91 ± 21,4 años; 261.694 (36,9%) eran mayores de 50 años.Solo 8.522 (1,39%) se habían sometido a pruebas de albuminuria en comparación con 264.684 (43,21%) de creatinina sérica, 140.492 (22,93%) de colesterol sérico, 263.381 (42,99%) de glucosa sérica y 226.448 (36,96%) de presión arterial. La albuminuria fue el único factor de riesgo cardiovascular evaluado con mayor frecuencia en hombres que en mujeres.La albuminuria, como otros factores de riesgo de ECV, se evaluó con mayor frecuencia en pacientes con DM (6,71% de los pacientes) o hipertensión (4,81%), pero la evaluación de la albuminuria siguió siendo subóptima en comparación con el 58% al 87% para otros factores de riesgo cardiovascular. Para los adultos con diabetes o hipertensión, la albuminuria se evaluó con mayor frecuencia en hombres que en mujeres.La evaluación de la albuminuria en los mayores de 50 años también fue subóptima, con un 2,24%, en comparación con un 31% a un 47% para otros factores de riesgo de ECV.La albuminuria y el FGe son necesarios para detectar ERC, lo que implica la determinación de albúmina y creatinina en orina y de creatinina en suero. A estos podemos agregar la evaluación de la presión arterial, el colesterol sérico (para la hipercolesterolemia familiar) y la glucosa sérica para la diabetes. La albuminuria fue el único factor de riesgo cardiovascular que se evaluó con mayor frecuencia en hombres (hasta casi un 60% más frecuentemente), lo que indica que la detección de ERC y riesgo de ECV en mujeres es subóptima. Este resultado es sorprendentemente consistente a lo largo del tiempo y en todos los grupos de edad. Esta es la primera vez que se revelan disparidades de género en la evaluación de la albuminuria. Conclusión: La albuminuria se evalúa con poca frecuencia, incluso en pacientes con alto riesgo cardiovascular, especialmente en mujeres.